Cultivation of Staphylococcus epidermidis in the Human Spaceflight Environment Leads to Alterations in the Frequency and Spectrum of Spontaneous Rifampicin-Resistance Mutations in the rpoB Gene - Fajardo-Cavazos, Patricia; Nicholson, Wayne L. (Frontiers in Microbiology, 2016)
Bacteria of the genus Staphylococcus are persistent inhabitants of human spaceflight habitats and represent potential opportunistic pathogens. The effect of the human spaceflight environment on the growth and the frequency of mutations to antibiotic resistance in the model organism Staphylococcus epidermidis strain ATCC12228 was investigated. Six cultures of the test organism were cultivated in Biological Research in Canisters-Petri Dish Fixation Units (BRIC-PDFUs) for 122 hours on orbit in the International Space Station (ISS) as part of the SpaceX-3 resupply mission. Asynchronous ground controls consisted of identical sets of cultures cultivated for 122 hours in the ISS Environmental Simulator at Kennedy Space Center. S. epidermidis exhibited significantly lower viable counts but significantly higher frequencies of mutation to rifampicin (Rif) resistance in space vs. ground control cultures. The spectrum of mutations in the rpoB gene leading to RifR was altered in S. epidermidis isolates cultivated in the ISS compared to ground controls. The results suggest that the human spaceflight environment induces unique physiologic stresses on growing bacterial cells leading to changes in mutagenic potential.